Death in Winter: Changing Symbolic Patterns in Southern Ontario Prehistory - Ramsden, Peter G. (Anthropologica, 2022)
In considering cultural changes in southern Ontario between about 250 B.C. and A.D. 1500, spanning the Middle and Late Woodland periods, an attempt is made to integrate settlement patterns, burials and ceramic decoration. It is suggested that long-term culture change can be understood as a result of the continual interaction between material culture, ritual, ideology, economy and social structure. The constant renegotiation of the meanings of material and ritual communication, including the accidental attribution of new meanings, can be a significant force for cultural change.